The correlation of breastfeeding support and preparation towards mother’s satisfaction on infant’s breastfeeding status - Widyaningrum, Rachmawati; Ayuningtyas, Cita Eri; Parisudha, Annisa; Handayani, Lina (International Journal of Public Health Science (IJPHS), 2024)
Besides the benefits of breastfeeding, the number of children exclusively breastfed was still low. The mother's breastfeeding decision might be influenced by breastfeeding support and preparation. The decision also might influence the mother's satisfaction and the child's well-being. Thus, to minimize the adverse effect of the decision, it is essential to identify the factors associated with mother satisfaction on their breastfeeding status. This study aimed to understand the correlation between breastfeeding support and preparation on mother's satisfaction with the infant's breastfeeding status. This study was a cross-sectional, observational study held in Yogyakarta, Indonesia. The inclusion criteria were the mother of a baby aged 6 to 24 months who lived in Yogyakarta City and was willing to join the research. A total of 150 respondents, mostly aged 19-40 years, joined the study. Spouse support is most influential on breastfeeding (BF) status. Mother's satisfaction with infant feeding choices was influenced by BF status, husband's support, and healthcare support. Husband support is essential for the mother to achieve exclusive breastfeeding and meet maternal satisfaction. Appropriate healthcare personnel support positively impacts maternal satisfaction by providing information and encouraging mothers to make informed infant feeding decision-making.